2009
DOI: 10.1115/1.3153310
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Motion in a Blood Vessel: Shear Stress Induced Endothelial Cell Injury

Abstract: Mechanisms governing endothelial cell (EC) injury during arterial gas embolism have been investigated. Such mechanisms involve multiple scales. We have numerically investigated the macroscale flow dynamics due to the motion of a nearly occluding finite-sized air bubble in blood vessels of various sizes. Non-Newtonian behavior due to both the shear-thinning rheology of the blood and the Fahraeus-Lindqvist effect has been considered. The occluding bubble dynamics lends itself for an axisymmetric treatment. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 21 publications
1
41
0
Order By: Relevance
“…610 Findings from this work predict surfactant promotion of bubble detachment from the vessel wall through modification of its adhesion characteristics 11 . These results were confirmed in vivo with direct observation of accelerated embolism bubble clearance from the microcirculation of the rat cremaster muscle after administration of exogenous surfactant.…”
Section: Introductionmentioning
confidence: 83%
“…610 Findings from this work predict surfactant promotion of bubble detachment from the vessel wall through modification of its adhesion characteristics 11 . These results were confirmed in vivo with direct observation of accelerated embolism bubble clearance from the microcirculation of the rat cremaster muscle after administration of exogenous surfactant.…”
Section: Introductionmentioning
confidence: 83%
“…The shear stresses and microjets produced by oscillating bubbles in a microvessel can directly impact the physiological functions of endothelial cells, red blood cells, and platelets. This results in vasocontraction, blood clot formation, and hemorrhage2627323334353637. The mechanism is similar to that of PDT and AVUT where microvessels are also destroyed by triggering the physiological functions of endothelial cells, red blood cells, and platelets.…”
mentioning
confidence: 96%
“…For the present study, two values of λ, namely, 0.9 and 1 are considered that represent nearly occluding bubble sizes. Our recent study (24) has shown that the hydrodynamic interactions between the finite sized bubble and the vessel wall remained nearly invariant for any further increases in bubble size beyond λ > 1.…”
Section: Methodsmentioning
confidence: 93%
“…While the previous work is limited to low fluid to gas viscosity ratios, the numerical methodology has been extended to solve the motion of a real gas bubble (27). The dynamics responsible for causing EC injury due to the motion of gas embolism has been clearly elucidated for the first time (2426). In (33), the computational simulations of bubble motion included the presence and transport of soluble surfactants both in the bulk and the blood-bubble surface.…”
Section: Introductionmentioning
confidence: 99%